COMPETENCIES FOR EMPLOYABILITY IN THE CIVIL CONSTRUCTION SECTOR: THE CASE OF CIVIL ARTISANS IN TANZANIA - Shukurani Mgaya; Josephat Itika; Ndikumana. D Emmanuel (ADISAM Publisher, 2023)
The paper assessed the extent to which the training and learning process of civil artisans under vocational education and training meets civil construction employers’ demanded competencies. Data were collected from trainers, learners, employees and employers through semi-structured interviews and structured questions. A qualitative exploratory approach was deployed with the help of MAXQDA2020 software. Content analysis was used to analyze documents and interview transcripts. It was found that to some extent the learning process captured employers to some extend despite several challenges on soft competencies which were seen demanded by employers. The article concludes that at least the hard competencies required for carpenters and masons were well covered by the curriculum and appreciated by employers although, outdated curriculum, inadequate teaching and learning resources, and exposure to practical work have a significant role to play and affect the employability of graduates. Despite, soft competencies including honesty, hard work, professionalism, and discipline were seen to be very important although there was no evidence that they were well imparted. Therefore it was suggested to collaborate with employers in imparting soft competencies.